Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Karyawan pada PT. PCS - Indah Wahyu Umami; Maulidyah Amalina Rizqi (STKIP PGRI SITUBONDO, 2023)
The research was conducted with the aim of knowing the relationship between the level of education and training variables based on employee performance. As a reference from the F-test value, the probable value is obtained on the variable F count (19,736) > F table (3,082), then the results of education (x1) and training (x2) can concretely affect employee performance (Y). from value Sig. ( 0.00517 ) < ( 0.05 ), then education ( x1 ) and the results of the value of training ( x2 ) also concretely affect employee performance (Y). In the stages and determination of variables from education and training it is useful to increase understanding in the world of work, but also, increase skills are obtained which facilitate the evaluation process and performance productivity for workers. So the hypothesis states that education and training have good added value and are used as benchmarks for employee performance. Evaluation of the research results explains that education variables and training variables have high potential in improving performance for workers, because they can make it easier for employees.